The Role of Human Capital Development in Enhancing Employee Performance: An Economic Perspective on Training, Remuneration, and Teamwork - Budi, Agha De Aghna Setya; Imronudin, Imronudin (International Journal of Economics Development Research (IJEDR), 2025)
This research investigates how training, compensation, and teamwork impact employee performance at PT Dan Liris. Adopting a quantitative method within a positivist framework, the study surveyed permanent employees with at least six months of tenure across various departments, including production, quality control, maintenance, human resources, and administration. Data were gathered using a structured questionnaire based on a five-point Likert scale and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that training, compensation, and teamwork all exert a significant positive effect on employee performance. Well-designed training programs enhance employees’ skills, knowledge, and adaptability, while equitable and competitive compensation boosts motivation and productivity. Additionally, effective teamwork underpinned by strong communication and collaboration promotes efficiency and collective accountability in meeting organizational objectives. The results indicate that the proposed model explains 64.8% of the variance in employee performance, demonstrating robust predictive capability. The study recommends that PT Dan Liris consistently improve training programs, uphold fair compensation practices, and foster a collaborative teamwork culture to optimize overall employee performance.